FOOD WASTE MANAGEMENT USING STATISTICAL ANALYSIS TO OBTAIN NEW FUNCTIONAL PRODUCTS - Gjore NAKOV; Zlatin ZLATEV; Nastia IVANOVA; Ivan DIMOV (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
A problem in food industry is the various types of waste that are produced during and after food preparation. In this article, mathematical studies have been implemented to obtain what amount of food waste is most appropriate for the enrichment of food and the production of new functional products. The subject of the study are cookies and the subject is the addition of Apple peel powder (APP). Physico-chemical, organoleptic characteristics and spectral indexes of biscuits were used as an input data. Vectors of the most informative features are selected, describing main indicators of the quality of cookies. Mathematical models have been developed to describe the relationship between the amount of APP and the weighting coefficients of the feature vectors. Using the partial least squares regression (PLS), principal component analysis (PCA), and factor analysis (FA) methods, it has been determined the optimum amount of APP for cookies preparation. The study found that using the Factor Analysis (FA) method performed better than using PCA and PLS. It has been found that the amount of apple residues in cookies is APP=23,6±1,3%, which can be considered as optimal. The proposed methods and tools have the potential to reduce food and waste losses. They are also one way to reduce production costs and improve food quality.